The Influence of Theology on Religious Understanding in South Sulawesi: A Study of the FKUB from the Perspective of Maslahah Maslahah Theory (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This article describes the influence of understanding purificative theology in the interpretation of religious teachings, especially in the FKUB (Religious Communication Forum) South Sulawesi, Indonesia. This research is descriptive in nature, conducting research on interfaith figures. One of the focuses of the study is the influence of Puritanism on interfaith figures. Puritanism is a theological view that believes that the interpretation of religious teachings must return to the original. Religious interpretation or interpretation is a product of the thoughts of individuals or religious institutions. One of the institutions that is very important in state and social life in Indonesia is the FKUB (Religious Harmony Forum). FKUB South Sulawesi as an institution that brings together various interfaith figures of course has dynamics in debates in dealing with issues in the field of religion. The results of the research show that religious figures at FKUB accept the puritan view by understanding it as an effort to purify religious teachings. But one religious figure, especially a Buddhist, considers religious purification to be utopian because there are difficulties in understanding what pure religious teachings actually are. In fact, as is known, the religious teachings that are currently developing are the result of interpretations while the founder of the religion is no longer alive. If there are differences between religious leaders in the FKUB, then each of them agrees to follow the existing rules and if there are no governing rules, then deliberation is prioritized. However, all religions agree that there are efforts to purify religious teachings.
Keywords: Theology; Puritanism; FKUB; religious interpretation